The Development of Realistic Mathematics Education (RME) Based Mathematics Learning Tools to Improve Problem Solving Ability in Elementary School - Umi, Faridatul; Yerizon, Yerizon; Syarifuddin, Hendra; Desyandri, Desyandri; Fitria, Yanti (STAI Hubbulwathan Duri, 2024)
This paper examines the development and analysis of mathematics learning tools based on Realistic Mathematics Education (RME) to enhance problem-solving skills in elementary school students. The research follows a development methodology, utilizing the Plomp development model, which includes three phases: preliminary research, development or prototyping, and assessment. Data collection methods comprised validation sheets, practicality test questionnaires, and question sheets. Both qualitative and quantitative analyses were performed on the collected data. Validity was assessed using a Likert scale, while practicality was evaluated through descriptive techniques and a Likert scale, and effectiveness was measured using a specific formula. The categorized percentage values were based on modified exposure levels. Additionally, the effectiveness of the learning tools was analyzed using student test scores, with hypothesis testing conducted via a t-test at an α level of 0.05. The content and language validity, as evaluated by validators, achieved a score of 92.54%, indicating a very valid category. Teacher responses rated the practicality of the learning tools at 97.85%, and student responses rated it at 95.86%, both indicating high practicality. The average final test score for students' problem-solving abilities was 94.69. These results suggest that the RME-based learning tools developed are highly suitable for use in fifth-grade in elementary school.